BETWEEN FORM, FUNCTION, AND TECHNIQUE: THE IMPORTANCE OF PHYSICS AND MATHEMATICS IN ARCHITECTURAL EDUCATION. (REMUNOM, 2026)
This article examines the insufficiency of basic Physics and Mathematics disciplines in the Architecture and Urbanism curricula in Brazil, advocating for their reinstatement as essential pillars. Although the National Curriculum Guidelines (DCNs) advocate for an education that integrates technical and humanistic knowledge, a gap is identified between this premise and actual practice. An analysis of the curricula from institutions in Rio Grande do Sul reveals that most do not offer such disciplines in their initial cycles. This deficiency, combined with the conceptual fragility of incoming students, undermines the understanding of advanced technical content, such as structural systems and environmental comfort. In professional practice, the lack of these fundamentals can result in projects with safety flaws, energy inefficiency, and increased costs. The study concludes by emphasizing the urgency of revising pedagogical plans, proposing the creation of contextualized disciplines, the establishment of prerequisites, and the adoption of leveling courses. The goal is to ensure a comprehensive education, enabling architects to achieve creative and technical syntheses aligned with contemporary demands for safe, sustainable, and functional buildings.